The Roles and Challenges of a Community-Based Waste Bank: A Case of Bank Sampah Teratai in South Tangerang, Indonesia - Juriani, Theresia; Anugrahini, Triyanti (Universitas Muhammadiyah Ponorogo, 2026)
Waste generation is an inevitable consequence of human activity and remains a pressing issue, particularly in urban areas. Rapid increases in waste volume, combined with inadequate infrastructure and ineffective disposal systems, have led to serious environmental and public health concerns. Community-based waste management strategies, such as waste banks, offer sustainable alternatives by integrating recycling programs, financial incentives, and citizen engagement. This study explores the roles and challenges of Bank Sampah Teratai (BS Teratai), a community-led waste bank in Pondok Pucung, South Tangerang, Indonesia. Using a qualitative approach, the research highlights BS Teratai’s contributions in raising environmental awareness, promoting economic empowerment through waste-based savings, and strengthening social cohesion. Verbatim quotes from participants illustrate how the initiative transforms waste from a burden into a valuable community asset. However, persistent challenges remain, including inconsistent community participation, limited storage capacity, unstable recyclable market prices, and the absence of proper facilities for hazardous and electronic waste. The COVID-19 pandemic further disrupted community involvement, exposing the vulnerability of grassroots efforts. This study emphasizes that waste banks can function not only as waste reduction tools but also as platforms for empowerment and behavioral change. The BS Teratai case offers valuable insights for replicating sustainable, community-based waste management models in other urban settings.